Assessment of the geometric profile of the Amplatzer and Cardioseal septal occluders by three dimensional echocardiography. Issue 4 (1st April 2001) - Acar, P; Saliba, Z; Bonhoeffer, P; Sidi, D; Kachaner, J
Abstract : OBJECTIVE: To apply three dimensional echocardiography to describe the geometric profile of the Amplatzer and Cardioseal occluders after deployment for closure of atrial septal defect. METHODS: 20 patients (mean (SD) age, 14 (5) years) were enrolled for transcatheter closure of a secundum atrial septal defect with the Amplatzer occluder (10) or with the Cardioseal occluder (10). The two populations were matched for the stretched diameter of the defect (mean 18 (6) mm). The profile of the two occluders was examined. RESULTS: Transoesophageal echocardiography did not show any residual shunts after Amplatzer occluder deployment, whereas three patients had a small residual leak after Cardioseal deployment. One patient had transient atrioventricular block with the Amplatzer device. The mean surface area of the Amplatzer occluder was 6.9 (2) cm 2, and that of the Cardioseal device 5.4 (3) cm 2 (p = 0.03). The mean volume of the Amplatzer occluder was 9.2 (1) cm 3, while that of the Cardioseal occluder was 3.5 (1) cm 3 (p < 0.0001). From the three dimensional views, the Cardioseal occluder looked like a flat square after deployment whereas the Amplatzer occluder took up a ball shape in the atrial cavity. CONCLUSIONS: Three dimensional views by multiplane transoesophageal echocardiography allow a realistic in vivo description of atrial septal occluders. The Amplatzer occluder, with its high geometric profile, allows complete closure of large atrial septal defects but with some risk of mechanical complications. Use of the Cardioseal device, with its small surface coverage and high residual shunt rate, should be limited to transcatheter closure of a patent foramen ovale or small atrial septal defects.